A Comparison of Two Radiography Scoring Methods Used by Rheumatologists and Radiologists in Patients with Established Rheumatoid Arthritis - Damjanovska Krstikj, Ljubinka; Jordanovska, Elena; Vasilevska Nikodinovska, Violeta (Synergy Publishers, 2015)
Background: There are numerous radiographic scoring methods in rheumatoid arthritis (RA). The scoring method Sharp/van der Heijde (SHS) is considered “a gold standard” for the assessment of the disease progression in RA. It is reliable but complex scoring method, which is time consuming and is used by well trained readers. The Simple Erosion Narrowing Score (SENS) was derived from the SHS method as an easier, quicker and reliable method for joint lesions scoring. Aim: The aim of the present work is to use and to evaluate the SENS method, for the first time in Macedonia, in comparison with SHS, and to test the agreement between the readers for the two scoring methods, in a group of patients with established RA. Materials and Methods: Evaluation of the patients included collection of demographic and clinical data, physical examination and calculation of the 28-joint Disease Activity Score (DAS-28). Laboratory tests and bilateral radiographs of the hands, wrists and feet were done in each of the patients. The radiographs were scored in pairs by two independent readers: rheumatologist and experienced radiologist. Results: The study group consisted of 54 RA patients. The mean age of the patients was 54,4 years. The average duration of the disease was 4,74 years with the mean DAS 28 score 5,0. The average radiography scores read by the rheumatologist and radiologist were 43,7 vs. 38,6 for the total SENS and 70 vs. 72 for the total SHS score. The interobserver reliability was calculated by the intraclass correlation coefficient (ICC) which was 0,77 for SENS and 0,88 for the SHS score. The intraobserver reliability was 0,76 vs 0,74 for the rheumatologist and radiologist, respectively. Conclusion: The performances of SENS method were good and the reading was very fast and easy. The agreement between the readers was higher for the more detailed SHS score.
Keywords: Rheumatoid arthritis (RA); Conventional radiography (CR); Sharp/van der Heijde score (SHS); Simple Erosion Narrowing Score (SENS); joint space narrowing (JSN)